A simple heuristics for optimisation of unbalanced multistage supply chain logistics associated with fixed charges. (7th March 2011) - Manimaran, P.; Selladurai, V.; Ranganathan, Rajesh
This paper presents a mathematical model and a simple heuristics-based solution procedure for the multistage supply chain logistics associated with the fixed charges. The objective of this paper is to select the optimum set of suppliers, plants, distribution centres (DC) to be opened and determine the quantities to be supplied to satisfy the customer demand with minimum distribution cost. Fixed charge problems arise in a large number of distribution systems. In many distribution problems, the transportation cost consists of fixed charges, which are independent of the amount transported and variable costs, which are proportional to the amount shipped. The problem chosen goes beyond the traditional mathematical programming and it becomes a non-polynomial (NP) hard while considering the fixed charges. We present a simple heuristics for optimisation of unbalanced multistage logistics system and compared it in terms of distribution cost with spanning tree-based genetic algorithm (st-GA) and improved Prüfer number encoding-based genetic algorithm (IPE-GA). The comparison reveals that the proposed heuristics is capable of providing better solutions.